Інформаційна демократія у країнах світу: порівняльний аналіз - Сіверська, В. О.; Siverska, V. O. (Східноєвропейський національний університет імені Лесі Українки, 2014)
Analysis of Information Democracy based foreign countries. Definition of “Information Democracy” and its components. Interpretation of scientists and their works of Information Democracy. Study of modern development of Information Democracy in government policy concerning the population. The problems that countries have and solutions that are used to improve information to citizens, their participation in the political process. Comparison Information Democracy of the world and Ukraine. Proposing of solutions to issues that meet genuine democratic standards of information to citizens for example of countries which lead the development of the Information Democracy.
Information Democracy in the world: comparative analysis
Роботу виконано на кафедрі міжнародної інформації СНУ ім. Лесі Українки
Keywords: інформаційна демократія; мир; визначення; вивчення сучасного розвитку; інформування громадян; участь у політичному процесі; Україна; Information Democracy; world; definition; study of modern development; information to citizens; participation in the political process; Ukraine